Use of a rhombic transposition flap in mandibular dermatosurgery - L. Miccio (PAGEPress Publications, 2023)
A 82 year old woman presented with a growing lesion of the right mandibular border. A clinical diagnosis of basal cell carcinoma was made and removal with a suitable border was planned